An Ethical Discussion About the Responsibility for Protection of Minors in the Digital Environment: A state-of-the-art review - Alves de Castro, Charles; Carthy, Aiden; O’Reilly, Isobel (Advances in Social Sciences Research Journal, 2022)
Many ethical questions have been raised regarding the use of social media and the internet, mainly related to the protection of young people in the digital environment. In order to critically address the research question “who is responsible for ethically protecting minors in the digital environment?”, this paper will review the main literature available to understand the role of parents, the government, and companies in protecting young people within the digital environment. We employed a holistic process that covers a state-of-the-art review and desk research. The article is divided into four sessions; (1) Government Policies from the European Union (EU) Perspective; (2) Parental Control; (3) An Overview of Companies and the Private and Self-Regulation Sectors; and (4) the Ethical Dilemma. Throughout, we reviewed specific topics regarding the potentially harmful content for young people within the digital environment, questioned how ethical concerns shape content and interactions online and discussed how internet parenting styles impact risks and opportunities for young people in the digital world. Finally, we analysed the research question contrasting it with the main findings in this review and offered recommendations.